2020
DOI: 10.1021/acsnano.0c09581
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Gradient Conductivity and Stiffness for Ultrasensitive Electronic Skins

Abstract: Hierarchical and gradient structures in biological systems with special mechanical properties have inspired innovations in materials design for construction and mechanical applications. Analogous to the control of stress transfer in gradient mechanical structures, the control of electron transfer in gradient electrical structures should enable the development of high-performance electronics. This paper demonstrates a high performance electronic skin (e-skin) via the simultaneous control of tactile stress trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 53 publications
1
116
1
Order By: Relevance
“…In principle, electrical resistance changes are governed by the structure and electrical features of piezoresistive materials, while material deformation critically depends on their geometry and mechanical properties 7 , 9 . Over the past few years, extensive investigations have focused on improving the detectability and/or sensitivity of piezoresistive sensors by optimizing the structural and electrical properties of sensing materials 8 , 10 14 . While conventional piezoresistive sensors made of bulk composites of conductive fillers and insulating polymers exhibit a low sensitivity 15 , recent studies have demonstrated that hierarchical nano/microstructured materials (e.g., cellular monolith/sponges 8 , 16 , 17 , nanomesh 18 , microdomes/micropillars/microspines 10 , 11 , 19 , bristled nanoparticles 12 , 20 , and microchannels/multilayers 21 , 22 ) provide decent sensing performance (sensitivity >100 kPa −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In principle, electrical resistance changes are governed by the structure and electrical features of piezoresistive materials, while material deformation critically depends on their geometry and mechanical properties 7 , 9 . Over the past few years, extensive investigations have focused on improving the detectability and/or sensitivity of piezoresistive sensors by optimizing the structural and electrical properties of sensing materials 8 , 10 14 . While conventional piezoresistive sensors made of bulk composites of conductive fillers and insulating polymers exhibit a low sensitivity 15 , recent studies have demonstrated that hierarchical nano/microstructured materials (e.g., cellular monolith/sponges 8 , 16 , 17 , nanomesh 18 , microdomes/micropillars/microspines 10 , 11 , 19 , bristled nanoparticles 12 , 20 , and microchannels/multilayers 21 , 22 ) provide decent sensing performance (sensitivity >100 kPa −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used method to sense these tactile stimuli is to convert them into electrical signals, including resistance or capacitance, which can be collected and processed by computer. Based on different mechanisms, the existing tactile sensors can be divided into resistive-type sensors [16,45,46] and capacitive-type sensors. [47,48] Resistive-type sensors normally transduce the above stimuli into a change in resistance, while the working principle of capacitance -based sensors is due to the change in capacitance induced by the stimuli.…”
Section: Various Sensing Functions Of E-skinsmentioning
confidence: 99%
“…Chunggi Baig and Hyunhyub Ko, [99] Ulsan University of Science and Technology in South Korea, proposed a gradient conductive structure based on a gradient mechanical structure and achieved high linearity, wide detection range (100 kPa), and ultra‐high pressure sensitivity (3.8×10 5 kPa −1 ) of e‐skin by accurately adjusting the current in the gradient conductive structure and transferring stress in the gradient mechanical structure. The PDMS microspheres used to achieve interlocking are coated with three layers of poly (3,4‐ethylene dioxythiophene): poly (styrene sulfonate) (PEDOT: PSS)/polyurethane dispersion (PUD) active layers with different conductivities, which are gradually increased from the outer to the inner layer by adding different amounts of ethylene glycol (Figure 7h).…”
Section: Design Of the Sensor Structurementioning
confidence: 99%